1990
DOI: 10.1084/jem.171.6.2063
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid accumulation and redistribution in rejecting rat kidney graft. Relationship to the transplantation edema.

Abstract: By using biotin-labeled proteoglycan core protein and an avidin-enzyme system, hyaluronic acid (HA) was visualized in rat kidney. In the normal kidney, HA was localized in the extracellular space of the inner medulla and increased markedly towards the papillary tip. No staining for HA was seen in the interstitial tissue of the cortex or the outer medulla. During the development of rejection of allogeneic renal grafts, a progressive increase in accumulated HA was seen in the interstitial tissue of the cortex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 34 publications
(52 reference statements)
9
75
0
Order By: Relevance
“…The synthesis ofa matrix rich in HA seems to be an important event during the early stages ofthe formation and remodelling of embryonic tissue and during wound repair (26). The matrix is thereby stabilized and cell infiltration and migration are stimulated (25)(26)(27)(28)(29). Thus, the early accumulation of HA and water in the myocardial interstitial tissue during infarction may facilitate the cell infiltration and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis ofa matrix rich in HA seems to be an important event during the early stages ofthe formation and remodelling of embryonic tissue and during wound repair (26). The matrix is thereby stabilized and cell infiltration and migration are stimulated (25)(26)(27)(28)(29). Thus, the early accumulation of HA and water in the myocardial interstitial tissue during infarction may facilitate the cell infiltration and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this question a similar investigation was performed in a series of rats receiving orthotopic kidney allografts, or syngeneic grafts in control animals. After allografting there was a progressive increase in the concentration of HYA to about twice the pretransplant values in the allograft after six days [30]. Localization studies with the biotin-labelled HYAbinding protein (HABP] showed that the overwhelming amount of HYA in the normal kidney was localized in the papillae, whilst virtually no HYA could be discerned in the cortex.…”
Section: Rejection Of Allograftsmentioning
confidence: 99%
“…Several studies have demonstrated that hyaluronan is highly abundant in the interstitium of the renal inner medulla in contrast to the low amounts seen in other regions of the kidney (4,13,18). Figure 6 illustrates the high level of hyaluronan accumulation in the rat inner medulla as revealed by Alcian blue staining.…”
Section: Concentrating Model Driven By Renal Pelvic Wall Contractionsmentioning
confidence: 99%